Aspek Pembuatan Model Listrik Hibrid Untuk Pemakaian Beban Rumah Tangga Di Kota Pekanbaru - Salman Alfarisi; Indra Yasri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The burden of household consumption in the city of Pekanbaru in each year isincreasing. PLN as a provider of primary electrical energy source load households dependon fossil fuels to produce electricity, but the amount of fossil energy resources availabilityis very limited because it requires the utilization of alternative energy sources although ona small scale for the initial process. New alternative and renewable energy is currentlywidely used, the use of renewable technologies, such as hybrid. Hybrid is an electric powersystem that combines multiple sources of electrical energy that can be used as a compactand integrated. Based on the above issues will require a feasibility analysis models ofhybrid power plant to the load of households in the city of Pekanbaru. This study usesHomer simulation system consisting of solar cells (PV), PLN, and Wind. Based on testinghybrid systems with the optimum configuration consists of PV and PLN with the total NetPresent Cost (NPC) amounted to $ 5.156 and the economic costs (COE) amounted to $0131 / kWh. The simulation results in supply by 37% from PLN and accounted for 63% ofthe solar energy.Keywords : renewable energy,Hybrid,Homer